Predictors of fossil fuel taxation attitudes across post-communist and other Europe - Jukka Sivonen (EMERALD GROUP PUBLISHING LTD, 2022)
Purpose: This study examines how the effects of three predictors, namely left-right political orientation, generalized trust and political trust, on fossil fuel taxation attitudes vary between post-communist and other European countries. Design/methodology/approach: By using European Social Survey (ESS) Round 8 data and ordinary least squares (OLS) regression, this paper studied the effects of the hypothesized predictors on fossil fuel taxation attitudes across post-communist and other European countries. The countries were analyzed both in group and individually.
Findings: The results showed that stronger left-wing orientation, higher generalized trust and higher political trust predict more support for fossil fuel taxation at the country group level in both post-communist and other Europe. However, the effects were generally speaking less consistent and significant in the countries of the post-communist Europe. By and large, the effect of political trust was the most significant and universal.
Originality/value: The findings contribute to the understanding how left-right political orientation and generalized trust have somewhat distinct effects on fossil fuel taxation attitudes in different European country contexts, while the effect of political trust is more universal across the continent.